MC_MoveAbsolute() 4th Order Real-Time Trajectory Generation Function Algorithm and Implementation - Pietrusewicz, Krzysztof; Waszczuk, Paweł; Kubicki, Michał (Applied sciences, 2019)
This paper presents the issue of generating motion trajectories in a digital servo drive in accordance with the PLCopen Motion Control standard. This standard does not limit the details of motion generation in the electromechanical systems, but indicates its interface and set of necessary parameters. Moreover, it is placed within a state machine, which allows the individual software elements to integrate with it seamlessly. This work discusses time-optimal point-to-point trajecto-ries, i.e., the initial and final reference speeds are zero, and they are compliant with the MC_MoveAbsolute() function defined in the PLCopen Motion Control standard. The smoothness of the resulting trajectory can be attributed to the use of a fourth order trajectory generator, which defines the bounds up to snap – the second derivative of acceleration. One of the aims of this article was to bridge the theoretical aspect of trajectory generation with the algorithms practical implementation, by the means of PLC code generation using the MATLAB/Simulink package.